Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{11}{12}-\left(\frac{2}{5}+x\right)=\frac{2}{3}\)
\(\frac{2}{5}+x=\frac{11}{12}-\frac{2}{3}\)
\(\frac{2}{5}+x=\frac{1}{4}\)
\(x=\frac{2}{5}-\frac{1}{4}\)
\(x=\frac{3}{20}\)
\(\frac{11}{12}-\left(\frac{2}{5}+x\right)=\frac{2}{3}\)
\(\Rightarrow\frac{2}{5}+x=\frac{1}{4}\)
\(\Rightarrow x=\frac{-3}{20}\)
Vậy \(x=\frac{-3}{20}\)
\(\frac{11}{12}-\left(\frac{2}{5}+x\right)=\frac{2}{3}\)
\(\frac{2}{5}+x=\frac{11}{12}-\frac{2}{3}\)
\(\frac{2}{5}+x=\frac{11}{12}-\frac{8}{12}\)
\(\frac{2}{5}+x=\frac{1}{4}\)
\(x=\frac{1}{4}-\frac{2}{5}\)
\(x=\frac{5}{20}-\frac{8}{20}\)
\(x=-\frac{3}{20}\)
11/12-(2/5+x)=2/3
2/5+x=11/12-2/3
2/5+x=1/4
x=1/4-2/5
x=-3/20
\(\frac{11}{12}-\left(x+\frac{2}{5}\right)=\frac{2}{3}\)
\(\Rightarrow x+\frac{2}{5}=\frac{1}{4}\)
\(\Rightarrow x=-\frac{3}{20}\)
11/12-(X+2/5)=2/3
X+2/5=11/12-2/3
X+2/5=1/4
X=1/42/5
X=-3/20
2/5 + x = 11/12 - 2/3
2/5 + x = 1/4
x = 1/4 - 2/5
x = -3/20.Vậy x= -3/20